2021
DOI: 10.3892/etm.2021.10243
|View full text |Cite
|
Sign up to set email alerts
|

Naringin attenuates rat myocardial ischemia/reperfusion injury via PI3K/Akt pathway‑mediated inhibition of apoptosis, oxidative stress and autophagy

Abstract: Naringin (NRG) has been reported to exert cardioprotective effects against multiple cardiovascular diseases, including lipopolysaccharide-induced and hyperglycemia-induced myocardial injury. However, the role of NRG in myocardial ischemia/reperfusion (I/R) injury remains unclear. In the present study, the PI3K/Akt pathway was investigated to evaluate the possible mechanisms underlying the roles of NRG in myocardial ischemia/reperfusion (I/R) injury. The levels of cardiac enzymes were measured by ELISA to evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…This technique affords end products ( Citrus fruits IntegroPectins) with higher water solubility, in which a great amount of bioactive compounds are adsorbed at the surface of pectin. Indeed, high levels of naringin (about 73 mg/g of extract) and other characteristic flavanones, as well as volatile compounds (such as limonene and alpha-linalool), have emerged from the phytochemical analyses [ 16 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…This technique affords end products ( Citrus fruits IntegroPectins) with higher water solubility, in which a great amount of bioactive compounds are adsorbed at the surface of pectin. Indeed, high levels of naringin (about 73 mg/g of extract) and other characteristic flavanones, as well as volatile compounds (such as limonene and alpha-linalool), have emerged from the phytochemical analyses [ 16 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study found that NAR had a significant advantage in improving MIRI. NAR alleviates MIRI in rats by inhibiting apoptosis, oxidative stress and autophagy through PI3K/Akt pathway [ 5 ]. The regulation of heat shock proteins 27 and 70, p-Akt/p-eNOS and MAPKs by NAR can inhibit myocardial injury and dysfunction after ischemia/reperfusion [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we can discuss, even if not exhaustively, about a putative improvement of the bioavailability. Moreover, we chose to evaluate the anti-ischemic cardioprotection, that has been previously demonstrated for naringin and naringenin [7,12,[24][25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the experimental results clearly demonstrated the dose-dependent cardioprotective activity of grapefruit IntegroPectin against ischemia/reperfusion injury, showing an efficacy comparable to the purified naringenin but with 10 times lower dose. Moreover, it was reported in the literature that also naringin possesses effective cardioprotection against several types of myocardial insults, yet at higher dose (in the range between 20-100 mg/Kg) compared to that found in grapefruit IntegroPectin [23][24][25][26][27][28].…”
Section: Cardioprotective Effects Of Grapefruit Integropectin In Ex V...mentioning
confidence: 99%